Relation between phonological awareness and systematic literacy instruction: Is conditionality one-way in consistent orthographies? - Želimir Ž. Dragić; Dijana Lj. Vučković (University of Belgrade, Teacher Education Faculty, 2020)
The aim of the research was to evaluate phonological awareness of the first grade pupils (N = 143) and to determine whether the start of systematic literacy instruction significantly enhanced this ability. The research is of comparative nature and it was implemented during the months of April and May of the school year 2017/18 in Banja Luka and Nikšić. The research question was: Does learning to read and write accelerate the development of phonological awareness or does development of phonological processing flow relatively independently from the start of a systematic literacy instruction? It has been hypothesized that learning to read and write significantly enhances the development of phonological awareness. Our subsamples are in the school systems according to the curricula which anticipate different start of systematic literacy instruction - in the first, that is, the second grades. We used the phonological awareness protocol as a research instrument. The results of the research indicate that there is a tendency - but not reliable enough evidence - that the start of literacy instruction accelerates the development of phonological processing skills. The results obtained on the tasks that demand deep phonemic awareness (word segmentation task) imply the conclusion that analytical exercises contribute to the development of phonemic awareness regardless of the start of the systematic literacy instruction.